Impact of Iliac Instrumentation on the Quality of Life of Patients With Adult Spine Deformity. Issue 13 (1st July 2018) - Martín-Buitrago, Mar Pérez; Pizones, Javier; Sánchez Pérez-Grueso, Francisco Javier; Díaz Almirón, Mariana; Vila-Casademunt, Alba; Obeid, Ibrahim; Alanay, Ahmet; Kleinstück, Frank; Acaroglu, Emre R.; Pellisé, Ferran
Abstract : Study Design: Retrospective comparative analysis of data collected prospectively in an adult spine deformity (ASD) multicenter database. Objective: To evaluate the impact of the iliac screws on the quality of life of ASD patients compared with those instrumented above the pelvis (L5/S1/S2). Summary of Background Data: The impact on patient's daily activities and functions, of immobilizing the sacroiliac joint with iliac screws for the treatment of ASD is still underexplored. Methods: Inclusion criteria were ASD patients with a long arthrodesis of at least eight levels and whose lowest instrumented vertebrae (LIV) were L5 or below. We analyzed the following preoperative and 2 years' follow-up variables: age, Cobb angle, coronal and sagittal alignment, number of instrumented levels, Oswestry Disability Index (ODI), Core Outcome Measures Index( COMI), Scoliosis Research Society-22 (SRS-22), and Short Form 36 (SF-36) questionnaires. Statistical analysis was performed with Mann–Whitney U test, and Wilcoxon test. Results: A total of 129 patients were included, and separated into two groups: "Iliac Yes, " with the LIV at the Ilium (N = 104), and "iliac No, " with the LIV at L5/S1/S2 (N = 25). Patients instrumented with Iliac screws were older ( x = 66 vs. 56 yr, P = 0.008), and had lower Cobb magnitude ( x = 31° vs. 45°, P = 0.019). No statistically significant differences were found in the health related quality of life (HRQOL) questionnaires prior to surgery or at 2-years' follow up. The "Iliac Yes" group significantly improved all radiographic and HRQOL scores parameters 2 years after surgery ( P < 0.005). While the "Iliac No" group failed to significantly improve (coronal balance, sagittal vertical axis, SF-36 Physical functioning, SF-36 General health, and COMI) ( P > 0.05) Conclusion: ASD patients instrumented with iliac screws significantly improved all their HRQOL questionnaires 2 years after surgery. The 2 years' postoperative HRQOL scores were similar in both groups, regardless of the sacroiliac joint immobilization. Therefore, with the currently available tools, we cannot state that iliac instrumentation has a negative influence on patient's quality of life. Level of Evidence: 4